Konsep Manusia dalam Penafsiran Bintu Syati Studi atas Kitab Maqal fi al-Insan Dirasah Qur’aniyah - Ahmad Zaeni; Dewi Purwanti; M. Toha Maulana (AL-MUFASSIR, 2020)
The present study scrutinizes Bintu Syati’s interpretation towards verses in Al-Qur’an concerning the concept of human and its interpretation method. This study employs a qualitative study through library data by using content analysis. The findings indicate that Bintu Syati relies on the method of hermeneutic interpretation by considering Al-Qur’an as a literary work as it speaks in each verses itself. The conclusion has been reached in line with the concept of human proposed by Bintu Syati’s interpretation method towards several verses concerning human. It can be inferred that what separates humans from other beings is the potential of al-Bayan where it is a way of expressing and explaining what is inside the heart, thinking and learning therefore humans have the right to become caliphs